Control of Post harvest waste of “Capsicum annuum” by Application of Natural Polymer glazer (International Journal of Food and Nutritional Sciences, 2023)
Thus, the application of mucilage as a natural polymers, extracted from the waste flowers of avenue roadside plants would be helpful in maintaining the quality of harvested vegetables as well as it might be helpful to reduce the losses caused during post harvest transport. The natural coater was prepared with the application of mucilage powder along with protein, lipid complexes. Spathodea campanulata mucilage improves the water content, relative water content, succulence and osmotic potential of Capsicum annuum, this will helpful to maintain the turgidity of fruits. The natural coater when applied to these Capsicum annuum, the postharvest shelf-life of vegetables increased, while due to presence of significant bonds of starch in the region of 1200 to700cm-1 and also turgidity is a sign quinon of freshness of vegetables and fruits. The application of various concentrations of natural coater to Capsicum annuum significantly improves the turgidity and water content of vegetables. This will helps to maintain the freshness and shelf life of Capsicum annuum. The further deterioration of the fruit during the storage of postharvest period of Capsicum annuum is useful in the improvement of the shelf-life and freshness of the vegetables during the course of marketing. Thus the application of Spathodea campanulata mucilage coating is beneficial for the pos-tharvest of the Capsicum annuum in future.